2010
DOI: 10.1227/neu.0b013e3181f8d1b2
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Malformations of the Brainstem Presenting in Childhood: Surgical Experience in 40 Patients

Abstract: Compared with adults, pediatric patients with BCSMs tend to have larger lesions and higher rates of recurrence (regrowth of residual lesion). Given the greater life expectancy of children, surgical treatment seems warranted in those with surgically accessible lesions that have bled. Outcomes were similar to those in our adult series of patients with BSCMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 18 publications
3
80
0
Order By: Relevance
“…Furthermore, studies differed in their hemorrhage definitions, the assumption of a congenital lesion, and neurological function evaluation methods. 1,2,4,14,24,30,35 In our study, we performed a prospective analysis of retrospectively collected data on the cohort of pediatric brainstem CMs with a stringent definition of hemorrhage and found that the annual hemorrhage rate was calculated to be 11.7% per patientyear, that both the presence of perilesional edema and a larger lesion size predicted poorer hemorrhagefree survival and a higher annual hemorrhage rate, and that prospective hemorrhage prevented complete neurological recovery (Fig. 2).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, studies differed in their hemorrhage definitions, the assumption of a congenital lesion, and neurological function evaluation methods. 1,2,4,14,24,30,35 In our study, we performed a prospective analysis of retrospectively collected data on the cohort of pediatric brainstem CMs with a stringent definition of hemorrhage and found that the annual hemorrhage rate was calculated to be 11.7% per patientyear, that both the presence of perilesional edema and a larger lesion size predicted poorer hemorrhagefree survival and a higher annual hemorrhage rate, and that prospective hemorrhage prevented complete neurological recovery (Fig. 2).…”
Section: Discussionmentioning
confidence: 89%
“…1,2,36,48 Most previous studies included both adult and pediatric patients, were limited by their retrospective nature, or encountered inherent referral biases in surgical series that compromised the comparability between studies and obscured the natural history of pediatric brainstem CMs. Furthermore, studies differed in their hemorrhage definitions, the assumption of a congenital lesion, and neurological function evaluation methods.…”
Section: Discussionmentioning
confidence: 99%
“…28,49,68 Preoperative hemorrhage risks are still the subject of controversy and have been insufficiently studied. Several factors have been correlated with hemorrhage, including sex (female), 6,9,51,63,69 age, 3,6,12,43 lesion location (deep-seated lesions), 17,41,44,56 large lesion size, 43 a history of previous ictus, 6,7,25,28,[40][41][42][43]56,57,66 and associated DVA. 1 A prospective, population-based cohort study demonstrated that female sex was a risk factor for the recurrence for cerebral CMs, but the annual rates of recurrence were not significantly different for brainstem lesions and lesions in other locations.…”
Section: Natural Historymentioning
confidence: 99%
“…3,4,31,32,54 Therefore, we retrospectively reviewed a single-center series of 242 cases of brainstem CM to determine the pre-and postoperative hemorrhage risk factors, clinical characteristics based on the location of the lesions, and long-term functional outcomes.…”
mentioning
confidence: 99%
“…Surgical excision of cavernous malformations relieves mass effect on surrounding brain and may be effective in controlling seizures, especially if surrounding hemosiderin-stained tissue is removed. Unfortunately, removal of lesions in the brain stem does not necessarily eliminate the risk of hemorrhage: there is a growing awareness of a moderately high rate of recurrence in this region and the spinal cord [233]. Whether recurrence is related to further growth of residual malformation or development of a new lesion remains to be determined.…”
Section: Prognosismentioning
confidence: 99%